The Malay Sultanates as the impetus for the formation of Malaysia - Wan Ahmad Fauzi, Wan Husain; Od., M. Anwar; Zulayti, Zakaria; Intan Maizura, Abd Rashid; Najuwa, Mohd Nasir; Irza Hanie, Abu Samah (Psychology and Education Journal, 2021)
This paper investigates the history of the Malay Sultanates. The study on the Malay Sultanates will effectively assist us in understanding the concept of Federation because it served as the impetus for the emergence of the Malay States which constitute what Malaysia is today. It is found that Malaysia was not a creation from the alleged social contract established by the so called `forefathers’ in many popular writings but it was the Malay Sultanates who had delegated some of their powers and executive rights for the formation of a strong central government